Replacement of Algebraic Loops in a Computer Aided Design Package CADoVS - Bartkevicius, S.; Sarkauskas, K. (Elektronika ir Elektrotechnika, 1998)
A method of replacement of linear algebraic loops from structure of a control system is proposed. The method is suitable for single and nested algebraic loops. Replacement increases total number of blocks of structure in number of input signals of replaced loops.